THE EFFECT OF ESG PERFORMANCE ON STOCK RETURNS: EVIDENCE FROM THE IDX ESG LEADERS INDEX - Rina Yulistia; Hendri Mauliansyah (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study examines the relationship between Environmental, Social, and Governance (ESG) performance and stock returns in the Indonesian capital market, using evidence from companies listed in the IDX ESG Leaders Index between 2018 and 2022. ESG ratings were collected from Bloomberg, Refinitiv, and corporate sustainability reports, and matched with stock return data. Multiple regression and correlation analyses were employed, controlling for firm size, industry sector, and market volatility. The sample comprised 30 firms consistently included in the index across the study period, representing a range of industries. The results indicate a significant positive relationship between ESG scores and stock performance. Firms with higher ESG ratings outperformed lower-rated peers by an average of 3% annually and exhibited greater resilience during the COVID-19 crisis. Governance emerged as the most influential dimension, while environmental and social factors showed sector-specific effects, particularly in consumer goods and renewable energy. These findings reinforce the view of ESG as both a financial driver and a risk mitigator in emerging markets. The study contributes to sustainable finance literature by providing evidence from Indonesia, where ESG research remains limited, and offers practical implications for investors, regulators, and corporate leaders to integrate ESG criteria into investment and business strategies.